2023
DOI: 10.3390/ijms24076852
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Response to DNA Damage: From DNA Repair to Polyploidy and Beyond

Abstract: A major challenge in treating patients with solid tumors is posed by intratumor heterogeneity, with different sub-populations of cancer cells within the same tumor exhibiting therapy resistance through different biological processes [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Polyploidy giant cancer cells (PGCCs) have been confirmed to possess cancer stem cell (CSC)-like characteristics, and give rise to progeny cells through asymmetric division which express epithelial-mesenchymal transition (EMT)-related markers thereby promoting invasion and migration [ 12 14 ]. Studies have shown that PGCCs generation was induced by anti-cancer therapies where the latter convert proliferating tumor into dormant cells [ 15 ]. The presence of PGCCs in OC has been preferentially reported in poor prognosis cancers participating in tumor relapse and therapy resistance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyploidy giant cancer cells (PGCCs) have been confirmed to possess cancer stem cell (CSC)-like characteristics, and give rise to progeny cells through asymmetric division which express epithelial-mesenchymal transition (EMT)-related markers thereby promoting invasion and migration [ 12 14 ]. Studies have shown that PGCCs generation was induced by anti-cancer therapies where the latter convert proliferating tumor into dormant cells [ 15 ]. The presence of PGCCs in OC has been preferentially reported in poor prognosis cancers participating in tumor relapse and therapy resistance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%